Famine process and famine policy - Hall-Matthews, D; Hall-Matthews, David (2002)
﻿ Ahmednagar District, in Bombay Presidency, was affected - along with much of South India - by a major drought in 1876-78, leading to famine relief by the Government of Bombay and considerable emigration and mortality. Recent literature, however, has suggested that famine is a complex, human and long-drawn-out process, rather than a sudden, natural phenomenon. This thesis seeks to identify that process among poor peasants in Ahmednagar between 1870 and 1884. It does so by examining their factors of production - land, capital and, to a lesser extent, labour - as well as markets in credit and the cheap foodgrains they produced, in order to locate both their chronic food insecurity and forces increasing their vulnerability over time. In this context, emphasis is given to the relationship of the British colonial state to the peasantry. The agrarian policies and agendas of the Government of Bombay are explored with regard to peasant vulnerability. It is argued that it failed to invest in production and infrastructure, while forcing peasants into competitive markets in which they were ill-equipped to compete. Despite a laissez-faire philosophy, it intervened to first promote, then penalise, usurious moneylenders, reducing the availability of credit. It also taxed peasants directly through the inflexible ryotwari land revenue system. In the crisis, peasants were not treated as famine victims and discouraged from accepting relief. The state can therefore be said to have contributed to the process of famine. It is argued that the propriety of colonial famine policies - and especially of other policies in the agricultural sector that undermined peasant food security - was widely discussed at different levels within the British state, from assistant collectors in Ahmednagar to secretaries of state in London. Attention is given to the way these debates were conducted and the process of policy-making analysed, concluding that the colonial hierarchy made it difficult for officers to be responsive to local problems.